Long-term isothermal oxidation behavior of two industrial polycrystalline nickel base alloys in air at 700 °C – Evaluation of intergranular oxidation distribution and kinetic. (1st August 2021) - Malacarne, R.; Mathieu, S.; Aranda, L.; Vilasi, M.; Desgranges, C.; Knittel, S.
Highlights: The oxidation behavior of IN718 and AD730 has been quantified at 700 °C up to 10 000 h. Rates are estimated by direct measurements and image analysis of SEM cross sections. The parabolic constants for external and grain boundaries oxidation are determined. Internal oxidation represents around 30 % of the total mass gain. Tests longer than 10 000 h is required to define the oxidation behavior of these alloys. Abstract: Chromia forming Alloy 718 and AD730™ have been submitted to isothermal long-term air exposure up to 10 000 h at 700 °C. The resulting very low specific mass gain led to consider two alternatives to determine the oxidation kinetics. Measurements of the external layer thickness and of the intergranular oxide amount were carried out on SEM micrographs evidencing the intergranular oxidation contribute around 30% to the total specific mass change. AD730™ with a thicker external scale and a higher amount of intergranular oxide showed a twofold faster oxidation rate than Alloy718. The results demonstrated the need of even longer tests.